Implantação dos procedimentos contábeis patrimoniais na administração pública de governos locais em Minas Gerais: A legitimidade normativa percebida por contadores públicos - Silva, Bruno Bueno da (2023)
The accounting harmonization process in the public sector has been adopted in recent years worldwide, as well as in Brazil. Faced with this scenario, Brazilian public sector organizations strive to implement equity-focused accounting, unlike the budgetary approach historically applied in the country. In the meantime, the entity designated to standardize and articulate the process of implementing asset accounting procedures in the public sector was the National Treasury Secretariat (STN, in Portuguese abbreviation), which stipulated deadlines with delimited actions for the public administration to incorporate such procedures to all federative entities (Union, states and municipalities). However, the literature discusses the legitimacy of the standards published by the STN, as it is clear that the main strategy considered by it is based on the publication of standards that, in turn, must be used by the target audience. Evidently, the adoption of such rules is still a challenge for public entities, due to the low legitimacy found by the actors responsible for their implementation. Therefore, this work analyzed the normative legitimacy of the Public Sector Patrimonial Accounting Procedures Implementation Plan (PIPCP, in Portuguese abbreviation) using the qualitative method, with data collection carried out through semi-structured interviews with public accountants, in accord with an interpretative position based on an analysis category. The results indicated that, for the adoption process achieve greater legitimacy on the part of those responsible for implementation, some actions would be necessary, such as normative complementation to include practical aspects; effective participation of the State Audit Courts (TCEs, in Portuguese abbreviation); existence of specific discussion groups; encouragement from senior management of the respective public organization; greater investments in computerized systems and motivational incentives for accountants; among others. Other factors not directly related to the standard, such as inspection and strong reaffirmation of TCEs, also significantly interfere with the degree of implementation of heritage procedures in the public sphere. Therefore, it becomes important to break with the paradigm that changes refer to a single and strict responsibility of the accounting sector, so that the multifaceted participation of other departments, added to the inclusion of informal networks represented by external organizations that promote training professional, emerges as a strategy to positively collaborate in the level of implementation of public accounting, with a patrimonial focus.